HNF-1a promotes pancreatic cancer growth and apoptosis resistance via its target gene PKLR. (18th February 2020) - Fan, Zhiyao; Fan, Kun; Deng, Shengming; Gong, Yitao; Qian, Yunzhen; Huang, Qiuyi; Yang, Chao; Cheng, He; Jin, Kaizhou; Luo, Guopei; Liu, Chen; Yu, Xianjun
Abstract: Pancreatic ductal adenocarcinoma is one of the deadliest malignant tumors, and many genes play important roles in its development. The hepatocyte nuclear factor-1a (HNF-1a) gene encodes HNF-1a, which is a transcriptional activator. HNF-1a regulates the tissue-specific expression of multiple genes, especially in pancreatic islet cells and in the liver. However, the role of the HNF-1a gene in the development of pancreatic cancer is still unclear. Here, we used immunohistochemical staining and real-time PCR to analyze HNF-1a expression in pancreatic cancer tissue. Stable cell lines with HNF-1a knockdown or overexpression were established to analyze the role of HNF-1a in pancreatic cancer cell proliferation and apoptosis by colony formation assay and flow cytometry. We also analyzed the L-type pyruvate kinase (PKLR) promoter sequence to identify the regulatory effect of HNF-1a on PKLR transcription and confirmed the HNF-1a binding site in the PKLR promoter via a chromatin immunoprecipitation assay. HNF-1a was found to be overexpressed in pancreatic cancer and promoted proliferation while inhibiting apoptosis in pancreatic cancer cells. PKLR was identified as the downstream target gene of HNF-1a and binding of HNF-1a at two sites in PKLR (−1931/−1926 and −966/−961) regulated PKLR transcription. In conclusion, HNF-1a is overexpressed in pancreatic cancer, and the transcription factor HNF-1a can promote pancreatic cancer growth and apoptosis resistance via its target gene PKLR .